Rapid processing of threatening faces in the amygdala of nonhuman primates: subcortical inputs and dual roles. (22nd March 2022) - Inagaki, Mikio; Inoue, Ken-ichi; Tanabe, Soshi; Kimura, Kei; Takada, Masahiko; Fujita, Ichiro
Abstract: A subcortical pathway through the superior colliculus and pulvinar has been proposed to provide the amygdala with rapid but coarse visual information about emotional faces. However, evidence for short-latency, facial expression-discriminating responses from individual amygdala neurons is lacking; even if such a response exists, how it might contribute to stimulus detection is unclear. Also, no definitive anatomical evidence is available for the assumed pathway. Here we showed that ensemble responses of amygdala neurons in monkeys carried robust information about open-mouthed, presumably threatening, faces within 50 ms after stimulus onset. This short-latency signal was not found in the visual cortex, suggesting a subcortical origin. Temporal analysis revealed that the early response contained excitatory and suppressive components. The excitatory component may be useful for sending rapid signals downstream, while the sharpening of the rising phase of later-arriving inputs (presumably from the cortex) by the suppressive component might improve the processing of facial expressions over time. Injection of a retrograde trans-synaptic tracer into the amygdala revealed presumed monosynaptic labeling in the pulvinar and disynaptic labeling in the superior colliculus, including the retinorecipient layers. We suggest that the early amygdala responses originating from the colliculo–pulvino–amygdalar pathway play dual roles in threat detection.